دور منظومة التميز الحكومي في تحسين عمليات التعليم والتعلم: دراسة تطبيقية على مدارس المجلس التعليمي (1) النطاق (2) وزارة التربية والتعليم بدولة الإمارات العربية المتحدة - Khuloud Mohamed Alzaabi; Nurkhamimi Zainuddin (Usuli Faqih Research Centre PLT, 2024)
Institutional excellence systems allow for the detection of weaknesses in the teaching and learning processes, and they also help to set and apply standards that predict the occurrence of errors, to search for ways to confront them to prevent errors before they occur, and to find advanced mechanisms that contribute to a change in the pattern of thinking about how to perform the current work to how The best performance. Accordingly, the study problem was identified in answering the following question: What is the role of the governmental excellence system in improving teaching and learning processes in the schools of the Educational Council (1) Scope (2) of the Ministry of Education? The study aimed to identify the extent to which the government excellence system (the fourth generation) is benefited from in improving the teaching and learning processes in the schools of the Education Council (1), the educational scope (2), of the Ministry of Education / United Arab Emirates. The importance of the study was that it sheds light on the topic of benefiting from the standards of the government excellence system in developing and improving the learning and teaching processes, by defining the study methodology, the stages and steps of the study, the study community, the study sample, and identifying the study tool, its validity and degree of stability, and then determining the treatment Statistics and study variables, and finally study procedures. Where the study followed the developmental descriptive approach, which is considered the most appropriate method for human research, and is based on describing the phenomenon, and analyzing it based on the information and data collected, analyzed, discussed and interpreted, and linking its implications with the use of statistical treatment used to answer the study questions. The study population consisted of the principals of the schools of the Educational Council (1), scope (2), at the Ministry of Education, their deputies, heads of educational units and coordinators of educational materials during the first semester 2018-2019, which numbered (125), and were distributed among (12) schools. The results of the study showed that the surveyed sample believes that the schools affiliated to the Educational Council (1) Domain (2) are developing electronic and smart infrastructure to support teaching and learning processes.